Literacy in the Modern World: Proceedings of the Symposium - Kuboni, Olabisi (Faculty of Education, University of the West Indies, 1992)
This document contains papers presented at the symposium, which attempted to focus attention on the issues of literacy at a level beyond that concerned with equipping people with rudimentary skills. The symposium sought to provide the community of educators and other concerned citizens with a forum to explore the issue at a more conceptual level. The papers are presented in three sections: Section I - Literacy, Functional Literacy; Section II – Reading and Writing; Section III – Literacy and the Oral Tradition.
Keywords: Literacy